Induction of apoptosis by pinostrobin in human cervical cancer cells: Possible mechanism of action - Jaudan, Alka; Sharma, Sapna; Malek, Sri Nurestri Abd; Dixit, Aparna (Public Library of Science, 2018)
Pinostrobin (PN) is a naturally occurring dietary bioflavonoid, found in various medicinal herbs/plants. Though anti-cancer potential of many such similar constituents has been demonstrated, critical biochemical targets and exact mechanism for their apoptosis-inducing actions have not been fully elucidated. The present study was aimed to investigate if PN induced apoptosis in cervical cancer cells (HeLa) of human origin. It is demonstrated that PN at increasing dose effectivity reduced the cell viability as well as GSH and NO2- levels. Condensed nuclei with fragmented chromatin and changes in mitochondrial matrix morphology clearly indicated the role of mitochondria in PN induced apoptosis. A marked reduction in mitochondrial membrane potential and increased ROS production after PN treatment showed involvement of free radicals, which in turn further augment ROS levels. PN treatment resulted in DNA damage, which could have been triggered by an increase in ROS levels. Decrease in apoptotic cells in the presence of caspase 3 inhibitor in PN-treated cells suggested that PN induced apoptosis via caspase dependent pathways. Additionally, a significant increase in the expression of proteins of extrinsic (TRAIL R1/DR4, TRAIL R2/DR5, TNF RI/TNFRSF1A, FADD, Fas/TNFRSF6) and intrinsic pathway (Bad, Bax, HTRA2/Omi, SMAC/Diablo, cytochrome C, Pro-Caspase-3, Cleaved Caspase-3) was observed in the cells exposed to PN. Taken together, these observations suggest that PN efficiently induces apoptosis through ROS mediated extrinsic and intrinsic dependent signaling pathways, as well as ROS mediated mitochondrial damage in HeLa cells.